2013
DOI: 10.1002/stvr.1508
|View full text |Cite
|
Sign up to set email alerts
|

Search‐based testing using constraint‐based mutation

Abstract: SUMMARYMany modern automated test generators are based on either metaheuristic search techniques or use constraint solvers. Both approaches have their advantages, but they also have specific drawbacks: Search‐based methods may get stuck in local optima and degrade when the search landscape offers no guidance; constraint‐based approaches, on the other hand, can only handle certain domains efficiently. This paper describes a method that integrates both techniques and delivers the best of both worlds. On a high‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Micheal et al [22], Levin and Yehudai [25], Joachim et al [27] indicated that GA outperforms other SBTDG methods e.g. local search or random testing.However eventhough they can generate test data with appropriate fault-prone ability [4,5], they fail to produce them quickly due to their slowly evolutionary speed. Recently, as a swarm intelligence technique, Particle Swarm Optimization (PSO) [6,7,8] has become a hot research topic in the area of intelligent computing.…”
Section: Introduction *mentioning
confidence: 99%
“…Micheal et al [22], Levin and Yehudai [25], Joachim et al [27] indicated that GA outperforms other SBTDG methods e.g. local search or random testing.However eventhough they can generate test data with appropriate fault-prone ability [4,5], they fail to produce them quickly due to their slowly evolutionary speed. Recently, as a swarm intelligence technique, Particle Swarm Optimization (PSO) [6,7,8] has become a hot research topic in the area of intelligent computing.…”
Section: Introduction *mentioning
confidence: 99%